Animal domestication in the high Arctic: Hunting and holding reindeer on the I͡Amal peninsula, northwest Siberia - Anderson, David G.; Harrault, Loïc; Milek, Karen B.; Forbes, Bruce C.; Kuoppamaa, Mari; Plekhanov, Andreĭ V. (Journal of Anthropological Archaeology, 2019)
The history of animal domestication in the Arctic is often represented as marginal or a weak copy of more complex pastoral situations in southern climes. This article re-assesses the classic archaeological site of I͡Arte 6 on the I͡Amal Peninsula of Northwest Siberia for markers of early Rangifer and dog taming and the emergence of transport reindeer husbandry at the start of the Iron Age. We critically examine published and unpublished Russian language material on this first millenium site, and evaluate the interpretations against three ethnoarchaeological models: herd-following, decoy-mediated hunting, and transport reindeer husbandry. Using new ethnographic, geoarchaeological, botanical, and palynological evidence, as well as a revised site chronology, we demonstrate that I͡Arte 6 was likely the home of several different types of adaptation over a much longer period of time than had previously been assumed. This leads us to question the standard models of reindeer pastoralism, and to argue for a renewed attention to the ways in which Rangifer are held and enticed into a long-term relationship with people, the possibility that canine domestication may have also been a key factor, and how these relationships leave imprints in the environmental record.
EPrint Processing Status: Full text deposited in DRO